2012
DOI: 10.5897/jdae11.034
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of gender involvement in agricultural production in Nigeria

Abstract: Agricultural sector is still the leading sector in Nigeria's ailing economy as it provides direct employment to about 75% of the population. This paper examines gender involvement in agricultural production as a means towards increased food sufficiency and consequently curbing food crisis. It critically identified the specific gender involvement in agriculture and gender inequality is noticed in the sector and this constitutes a bottleneck to development, calling for a review of government policies on agricult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 1 publication
1
2
0
Order By: Relevance
“…The very good thing across locations is that all the family members are involved in managing the apple trees. In conformity with this research result, Feyisa and Megersa [26] and Mohammed and Abdulquadri [27] reported that the involvement of women in fruit crop production is paramount ranging from harvesting to marketing.…”
Section: Apple Planting and Production Systemssupporting
confidence: 71%
“…The very good thing across locations is that all the family members are involved in managing the apple trees. In conformity with this research result, Feyisa and Megersa [26] and Mohammed and Abdulquadri [27] reported that the involvement of women in fruit crop production is paramount ranging from harvesting to marketing.…”
Section: Apple Planting and Production Systemssupporting
confidence: 71%
“…Results also revealed maximum household of 41.67 % (4-6 persons) followed by 7-9 (30.83 %) persons, with farming experience of 7-9 years (34.2 %) and 10-13 years (24.2 %). The domination of married male was associated with energy sapping physical and manual activities involved in land clearing, tillage, planting inter alia against relatively less activities of weeding, harvesting, processing, marketing and preservation for female (Asumugha, Kormawa and Haan, 2009;Mohammed and Abdulquadri, 2012). Similarly, Ejechi et al (2018) reported lack of funds for high cost of inputs as an important impediment for relatively low women participation while Asumugha et al (2009), supported result of study when they reported average household of six and farm size of 0.75 to 3 ha, jointly owned or only 20 % belonging to women in Southern…”
Section: Resultsmentioning
confidence: 99%
“…Apart from these viewpoints, some other farmers claimed that incessant fooding (5%) and extreme high temperature (3%) are prominent indicators of the change in the climate. Te authors of [31,40,41] had reported diverse interpretation of what CC is to diferent individuals in Nigeria. Tese include the pattern of rainfall, temperature and long dry season as noted here.…”
Section: Respondents' Interpretation Of What Climate Meanmentioning
confidence: 99%